Solid-Phase Synthesis of Nitrogenous Heterocycles - Krchňák, Viktor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The series Topics in Heterocyclic Chemistry presents critical reviews on present and future trends in the research of heterocyclic compounds. Overall the scope is to cover topics dealing with all areas within heterocyclic chemistry, both experimental and theoretical, of interest to the general heterocyclic chemistry community. The series consists of topic related volumes edited by renowned editors with contributions of experts in the field. All chapters from Topics in Heterocyclic Chemistry are published Online First with an individual DOI. In references, Topics in Heterocyclic Chemistry is abbreviated as Top Heterocycl Chem and cited as a journal.
Solid-Phase Synthesis of Heterocycles in Practice -- Solid-phase synthesis of seven-membered heterocycles with two nitrogen atoms -- Intramolecular N-Acyl-Iminium Cascade (INAIC) Reactions in Cyclization of Peptide-like Molecules -- Advances in Metal-mediated Solid-phase Synthesis of Heterocyclic Compounds -- Intramolecular Arylation of 2-Nitrobenzenesulfonamides: A Route to Diverse Nitrogenous Heterocycles.
Keywords: Chemistry, Organic; Chemistry, Technical; Inorganic chemistry; Organic Chemistry; Industrial Chemistry; Inorganic Chemistry